Pendampingan Moderasi Beragama - Landasan Moderasi dalam Tradisi Berbagai Agama dan Implementasi di Era Disrupsi Digital - Mahdir Muhammad; Rahmad Sadli; Suparwany (JKA, 2024)
Religious Moderation Assistance is a crucial effort in addressing the challenges of pluralism and intolerance in the era of digital disruption. This study examines the foundations of moderation within various religious traditions and how these principles can be implemented in the current digital context. Through a qualitative approach, this research explores the understanding and practices of religious moderation in Islamic, Christian, Hindu, and Buddhist traditions, and analyzes how digital technology impacts the dynamics and application of moderation. Findings indicate that while there are differences in moderation approaches across religions, there are common principles that can guide the promotion of tolerance and interfaith dialogue. Implementing religious moderation on digital platforms requires strategies that integrate values of wisdom and empathy, as well as ongoing education to address potential conflicts and strengthen social cohesion. This study provides recommendations for developing assistance programs that can optimize the role of technology in supporting religious moderation and enriching intergroup interactions in society